Academic literacy development and professional identity construction in non-native English-speaking novice English language teachers - Chen, Mo; Zhang, Wenli; Zheng, Qun (Frontiers in Psychology, 2023)
Studies examining students’ academic literacy development have received increasing attention in the past two decades, with exponential growth in the literature since 2010. Despite this, there have been relatively few empirical studies on novice teachers’ academic literacy learning process and the construction of teachers’ professional identities. To address this issue, this study employed a longitudinal narrative inquiry to trace and evaluate the professional identity construction of two Chinese novice language teachers as they developed academic literacy in their master’s and doctoral programs in the United States. The study adopted a Community of Practice (CoP) framework and drew upon various data sources, such as both novice teachers’ coursework, reflection journals, statements of teaching philosophy, and other supplementary documents, to evaluate how each participant was socially engaged (or disengaged) in a new language education community and how they developed professional identities as language teachers in this process. The findings indicate that the pedagogical knowledge and theories acquired by both participants during their graduate studies informed their teaching methods and promoted their development of a researcher-teacher identity. In addition, the longitudinal data allowed for tracking changes in both participants’ self-efficacy and emotions. While the stories of both novice teachers described the evolution of their teaching beliefs throughout their graduate studies, their narratives also highlighted a lack of micropolitical literacy training at the graduate level. This study contributes to our understanding of the connection between academic literacy development and the formation of teacher professional identity by shedding light on novice language teachers with a non-native English-speaking background. The implications for future research are also provided.